Pengatuan Hukum Terhadap Narkotika Jenis-Jenis Baru yang Belum Terdaftar - Hakim, Rizky Maulana (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
We realize that in the community, it is still close to the night world which can plunge the nation's next generation, through drinking, gambling, and especially Narcotics. There are many rules related to this problem, it is still possible that the minimum knowledge of the community is what causes users to become victims of the rigors of using drugs.In discussing this paper, we will take and discuss the theme of "Legal Certainty and Role of Laws on Narcotics (Narcotics and Drugs / Hazardous Materials) by Users and Distributors." The purpose of accepting this paper is, first, to be agreed by the reader which can be understood about the dangers that need to be discussed regarding the subjectivity of the drug itself; secondly, asking the reader to get a clue about actually addressing the urgency about the distribution of drugs; round, which is about knowing what the rules of the law and also the awareness in the surrounding community.Keywords: Narcotics, Role of Laws, Problem, Minimum Knowledge, awareness